2017
DOI: 10.1111/zph.12402
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistant Escherichia coli in southeastern Australian pig herds and implications for surveillance

Abstract: SummaryTo investigate public health implications of antibiotics to control post-weaning scours, we surveyed 22 commercial pig herds in southeastern Australia. Fifty faecal samples per herd were collected from pre-and post-weaned piglets. Presumptive Escherichia coli isolates were confirmed by MALDI-TOF MS. Isolates (n = 325) were screened for susceptibility to 19 veterinary antibiotics using MIC broth microdilution. All 325 E. coli isolates underwent further testing against 27 antibiotics used in human medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
0
25
0
2
Order By: Relevance
“…However, the results of the current Australia-wide survey suggest that ceftiofur-resistant commensal E. coli are not dominant coliforms in the gut of slaughter age pigs that are likely to be isolated during AMR surveillance programs. Nevertheless, the emergence and recent detection of ceftiofur-resistant E. coli containing AmpC and ESBLs (Abraham et al, 2015 ; van Breda et al, 2018 ) confirms that off-label use of ESCs should be more critically evaluated by the Australian industry, as has recently occurred in Denmark (Agersø and Aarestrup, 2013 ). The Danish Agriculture and Food Council recommended a voluntary ban on the use of ESCs in pigs following increased detection of ESBL resistance genes in swine production facilities (Agersø and Aarestrup, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the results of the current Australia-wide survey suggest that ceftiofur-resistant commensal E. coli are not dominant coliforms in the gut of slaughter age pigs that are likely to be isolated during AMR surveillance programs. Nevertheless, the emergence and recent detection of ceftiofur-resistant E. coli containing AmpC and ESBLs (Abraham et al, 2015 ; van Breda et al, 2018 ) confirms that off-label use of ESCs should be more critically evaluated by the Australian industry, as has recently occurred in Denmark (Agersø and Aarestrup, 2013 ). The Danish Agriculture and Food Council recommended a voluntary ban on the use of ESCs in pigs following increased detection of ESBL resistance genes in swine production facilities (Agersø and Aarestrup, 2013 ).…”
Section: Discussionmentioning
confidence: 97%
“…Other reports soon followed (Barton, 2014 ). A recent Australian regional survey of fecal samples from 22 Australian commercial pig farms found 5.2% of E. coli isolates were resistant to ceftiofur (van Breda et al, 2018 ). The emergence of some level of non-susceptibility to ceftiofur in Australian herds is not unexpected, given previous reporting of “off-label” use in individual pigs, which is assumed to be for the treatment of ETEC infection (Jordan et al, 2009 ), raising concerns of the potential for cross-transfer of ceftiofur non-susceptibility to humans via the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive analysis by Klein et al, more than 200 E. coli strains across eight European countries were assessed for their resistance against dozens of antibiotics: results showed a considerable resistance towards antimicrobial compounds, including amoxicillin [19]. Other studies reported similar results, with MIC values for different E. coli strains equal to or greater than 64 mg/L for neomycin, ampicillin, and tetracyclines, proving an established or increasing spread of resistance genes [20][21][22][23]. E. coli resistance to penicillin G and lincomycin is also reported [20].…”
Section: Discussionmentioning
confidence: 99%
“…Given the uncertainty about which testing regimen would be ideally suited for a large national food safety screening program for MDR contamination [ 9 – 13 ], we believe our methodology was a practical approach that is potentially relevant and meaningful to retail consumers and which could be up-scaled without the need for major infrastructure or specialised training. In comparison, all previous published Australian studies have assessed non-meat items such as animal faeces or eggs [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%